Usnea dasaea, a further new addition to the Lichen Flora of Tamil Nadu State, India - Mariraj, Murugan; Kalidoss, Rajendran; Vinayaka, Kanivebagilu Shankaranarayana; Nayaka, Sanjeeva; Ponnusamy, Ponmurugan (Current Botany, 2020)
The present study addresses the addition of one new fruticose lichen species for the first time to the state of Tamil Nadu in Western Ghats, India. Usnea dasaea Stirt. is a new occurrence in Tamil Nadu. Descriptions of identification keys and distributions of such new species in south India provide useful information for identification. The new species addition of such lichen was identified and deposited at lichen herbaria, National Botanical Research Institute, Lucknow, Uttar Pradesh, India and Bharathiar University, Coimbatore, Tamil Nadu, India for further studies.